2014
DOI: 10.3233/ch-131675
|View full text |Cite
|
Sign up to set email alerts
|

Identification of early complications following pancreas and renal transplantation using contrast enhanced ultrasound (CEUS) – first results

Abstract: AIM: Identification of acute and subacute complications following pancreas and renal transplantation using contrast enhanced ultrasound (CEUS) in comparison with Magnetic Resonance Tomography (MRI), Computed Tomography (CT), Digital Subtraction Angiography (DSA) or Ultrasound (US). The study evaluated whether CEUS could confirm the preliminary diagnosis or even provide additional information, relevant for the therapeutic strategy. MATERIAL AND METHODS: Retrospective evaluation of 19 patients (13 male, 6 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 17 publications
1
22
0
1
Order By: Relevance
“…This study also demonstrated the potential advantage of GLCM analyses to evaluate vascular damage in resource‐challenged settings where contrast enhancement may not be available. This study adds to the repertoire of some recent studies where vascular anatomy has been assessed after liver transplantation. Our study correlates the ultrasound imaging with the molecular changes during ex vivo storage of livers for the first time.…”
Section: Discussionmentioning
confidence: 94%
“…This study also demonstrated the potential advantage of GLCM analyses to evaluate vascular damage in resource‐challenged settings where contrast enhancement may not be available. This study adds to the repertoire of some recent studies where vascular anatomy has been assessed after liver transplantation. Our study correlates the ultrasound imaging with the molecular changes during ex vivo storage of livers for the first time.…”
Section: Discussionmentioning
confidence: 94%
“…In doing so, it provides a qualitative assessment of lesion hemodynamic significance by identifying normal, delayed, diminished, or not detectable liver parenchymal perfusion. 1,20,21 Evaluating PVS with cross-sectional studies, such as contrast enhanced computed tomography (CT), or magnetic resonance imaging (MRI), is limited, as these exams are typically not dynamic (►Fig. 1D).…”
Section: Imaging Workupmentioning
confidence: 99%
“…39 In challenging settings, CEUS is employed with high diagnostic accuracy for PVT (97--100%). 21,38,40 Rennert et al demonstrated the diagnostic validity of CEUS to be comparable to magnetic resonance angiography (MRA) and computed tomography angiography (CTA), when employed at experienced centers. 21…”
Section: Incidence and Presentationmentioning
confidence: 99%
“…Relevant data extracted from all 13 studies are summarized in table 1 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Only two studies involved more than 100 cases for CEUS evaluation.…”
Section: Study Characteristicsmentioning
confidence: 99%